Building Adolescent Attitudes In Preventing Sexually Transmitted Infections In Man 1 Jombang: Membangun Sikap Remaja Dalam Pencegahan Infeksi Menular Seksual Di Man 1 Jombang - Rodiyah, Rodiyah; Andayani, Sestu Retno Dwi (Al-Hijrah Indonesia, 2022)
Sexually transmitted infections (STIs) are transmitted mainly through sexual contact. The World Health Organization (WHO) stated in 2016 that more than 1 million people suffer from STIs every day. STIs has a significant impact on sexual and reproductive health around the world. Complications from STIs can cause infertility, pregnancy disorders, growth disorders, cancer, and make it easier for someone to get infected with human immunodeficiency disease (HIV). This community service aims to increase students' knowledge about STIs. This counseling was carried out at MAN 1 Jombang with 100 students. Outreach materials include definitions, types of IMS, modes of transmission, signs and symptoms, complications, and prevention of STIs. Student knowledge before counseling is in the less category and after counseling is in a good category. MAN students are expected to be the spearhead in disseminating counseling information to families and communities to reduce the incidence and transmission of STIs in the community.